Developing an Ubuntu-infused e-commerce business model for South African small businesses based on a holacratic organisational structure - Nkuna, Cliff (Graduate School of Business (GSB), 2025)
South Africa's e-commerce industry is one of the better performing industries in the African continent. As with other technologies, e-commerce has the potential to help the country leapfrog ahead and help address the challenge of unemployment, simultaneously contributing towards improving the country's overall economic performance. This can be realised by bolstering e commerce and entrepreneurship through innovation among small and medium size businesses. This study focuses on e-commerce as one of the technologies that South Africa can invest in to contribute positively towards sustainable job creation, with the benefit of improved gross domestic productivity (GDP). A mixed methods approach was undertaken to understand the enablers and inhibitors of e-commerce in South Africa, with the intention of using this understanding to develop a business model that is suitable for South Africa's e-commerce industry and to help unlock its full potential. To this effect, eight participants who are entrepreneurs were interviewed. The entrepreneurs consisted of two groups that either utilise e-commerce as part of their business operations, and those that do not. Their contributions in the findings of the qualitative study were subjected to quantitative research through a survey study that was based on 65 respondents. These respondents were selected based on a convenience sampling method, and as a final exercise, the insights gleaned from both studies were analysed and incorporated into the business model. The e-commerce business model presented herein incorporates the communitarian values of Ubuntu, which is the prevalent axiological system in South Africa. In the business model Ubuntu is blended with the self-governance organisational structure of holacracy. This complements the collaborative and self-organisation trait of South African communities, which allows for the economic pursuits of an e-commerce initiative to reflect the nature of the societies in which it co-exists.